Kontribusi Soft Skill dalam Mengembangkan Kepercayaan Diri Siswa - Ahmad Sholihin; Heri Kurnia; Joko Wahono (HK Publishing, 2025)
Self-confidence is an important aspect during senior high school. Because self-confidence is related to better academic performance, positive social involvement, and readiness to enter the workforce or higher education. However, in reality, some students feel insecure both at school and outside of school. Therefore, this research answers whether these two variables are relevant. This research aims to find out how much soft skills contribute to the development of self-confidence in students using quantitative descriptive methods at SMA Negeri 7 Yogyakarta from April to May 2024 involving 158 students as samples taken using simple random sampling techniques using the program SPSS version 23 as a tool for processing data. Based on the results of hypothesis testing, show that the independent variable is proven to contribute significantly to the dependent variable, which means that there is a positive contribution between students' mastery of soft skills and students' self-development, which has implications for the need to master soft skills to support the achievement of students who have strong character. It is hoped that mastery of soft skills will be supported by all parties, including teachers, schools, and parents. Keywords: confident; education; soft skill.